German banks and the modernization of the small firm sector: long-term finance in comparative perspective - Sigurt Vitols (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1995)
This paper analyzes the contribution of the German banking system to the modernization of small and medium-sized enterprises (SMEs) in industry. The simultaneous greater relative importance of and relatively high wages in German SMEs appear to be paradoxical in terms of dual labor market theory, which claims that lower wages and greater flexibility in the use of labor are important for helping small firms compensate for their constrained access to capital, R&Dk and skills resources relative to large firms. This paper suggests that the successful modernization of the German small firm sector despite pressure from below from industry-level wage bargaining and strong job protection can be attributed to support from above in terms of an institutional infrastructure helping small firms overcome the organizational deficiencies they face relative to large firm. The decentralized provision of long-term finance and sophisticated financial services for the modernization of SMEs is enabled by a three-tiered federalist form of corporatist organization in the cooperative and savings banks sectors, in which smaller banks at the bottom tier of the organization receive access to refinancing on capital markets and specialized services – normally only available to large banks – through the upper tiers of the banking organization. – – Gegenstand dieses Papiers ist der Beitrag der deutschen Kreditinstitute zur Modernisierung des Mittelstands im Verarbeitenden Gewerbe. Die im internationalen Vergleich große relative Bedeutung der mittelständischen Unternehmen und ihr gleichzeitig niedriges Lohngefälle gegenüber Großunternehmen erscheint im Leichte der dualen Arbeitsmarkttheorie als paradox. Danach müßten im Mittelpunkt der Personalpolitik der mittelständischen Unternehmen ein niedrigeres Lohnniveau und eine größere Flexibilität stehen als Ausgleich für den gegenüber Großunternehmen begrenzteren Zugang zu Kapital, FuE und Weiterbildung. In diesem Papier wird die Meinung vertreten, daß die durch hohe Löhne und starken Arbeitsschutz erzwungene Modernisierung des deutschen Mittelstandes durch eine institutionelle Infrastruktur unterstützt worden ist. Der Zugang des Mittelstandes zu dem für die Modernisierung wichtigen langfristigen Kapital und zuz speziellen Finanzierungsmöglichkeiten wird durch eine dreistufige forderalistische Form der korporatistischen Organisierung in dem Sparkassen- wie in dem Kreditgenossenschaftssektor ermöglicht. Keinere Kreditinstitute auf lokaler Ebene erhalten eine langristige Refinanzierung am Kaptialmarkt, Qualifizierungsmaßnahmen und besondere Finanzdienstleistung – die normaerweise nur großen Banken zugänglich sind – durch die regionalen und nationalen Ebenen ihrer jeweiligen Verbundorganisationen.
Keywords: 330; Klein- und Mittelunternehmen; Wirtschaftliche Anpassung; Bank; Deutschland; Klein- und Mittelunternehmen